Wide-dynamic-range cantilever magnetometry using a fiber-optic interferometer and its application to high-frequency electron spin resonance spectroscopy. (27th October 2016) - Takahashi, Hideyuki; Okamoto, Tsubasa; Ohmichi, Eiji; Ohta, Hitoshi
Abstract: We present a method of broadening the dynamic range of optical interferometric detection of cantilever displacement. The key idea of this method is the use of a wavelength-tunable laser source. The wavelength is subject to proportional-integral control, which is used to keep the cavity detuning constant. Under this control, the change in wavelength is proportional to the cantilever displacement. Using this technique, we can measure large displacements (>1 µm) without degrading the sensitivity. We apply this technique to high-frequency electron spin resonance spectroscopy and succeed in removing an irregular background signal that arises from the constantly varying sensitivity of the interferometer.